EKSPATRIAT: FENOMENA PENUTUR BAHASA BALI DARI MANCANEGARA - Made Suardika Jaya; Dewa Putu Krisnawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The existence of expatriates in a particular country can provide its own colour and nuance for the country itself. In Indonesia, especially in Bali, there are a number of expatriates who stay on vacation, to work or take education. A lot of expatriates who intensively visit or do live in Bali, especially those who are interested in Balinese culture, are able to communicate in Balinese proficiently. To obtain information related to expatriates who are able to communicate in Balinese, interviews were carried out with four samples who are four expatriates who intensively visited or settled in Sanur and Ubud for at least three years. There are several factors which make them interested in learning Balinese language (basa Bali alus and basa Bali kepara). With all the efforts they put in, they are eventually able to pronounce, utter and communicate in Balinese fluently even though their mother tongue accents can still be heard.Keywords: expatriates, communication, Balinese language